MACD And Excess Returns: A Study Of Malaysian Stock Market - Hock, Goh Soon (2007)
This study investigate the ability of the Greald Appel\'s Moving Average Convergence-Divergence (MACD) indicator, as filter technique to derive excess returns (ER) over medium period (1 year) from sector of Main Board of Malaysian stock market under the consumption that the trend sector is known. The trading rules used are designed to exploit secondary price fluctuations of the Dow\'s Theory coupled with the sector momentum and positive autocorrelation of price changes.